Unicentric Castlemans disease presenting as a neck swelling: a case report - Ravishankar, K. S.; Subramanian, Atreya M. (International Surgery Journal, 2019)
Castleman’s disease is an uncommon entity which is characterized by lymphadenopathy either at a single focus or at multiple sites.Due to the similar clinical picture of other disorders including tuberculous lymphadenitis, lymphoma and other cases of generalized lymphadenopathy like AIDS a diagnosis of castlemans disease. The unicentric form may resemble any generalized swelling such as a lipoma. In this case we discussed an 18 yr old girl presenting with a large neck swelling in the posterior triangle which clinically resembled a lipoma. The CT showed a uniformly enhancing homogenous lesion. After an excision biopsy, the histopathology revealed it to be castleman’s disease of the hyaline vascular type. The literature reveals that although rare castlemans disease can be unicentric or multicentric and can involve multiple sites including the axilla, mediastinum and retroperitoneum. Most cases of the unicentric disease are completely cured with an excision biopsy. The multicentric disease may need chemotherapy, radiation or immunomodulating drugs. In conclusion, one must keep a differential of castlemans disease in mind when presented with any case of lymphadenopathy.